Transition to parenthood in the social context, extended family and friends, on pregnancy in late age. (Journal of Statistics on Health Decision, 2020)
Background: Currently, there has been an increase of late motherhood, especially in western industrialized countries, mothers are having her first child after 35 years old. This phenomenon is associated with increase women´s investment in their academic career, seek financial and marital stability, postponing the decision to be a mother. Women postpone maternity and decide to have their first child at an advanced age as evidenced in the statistics, mean age of women at childbirth increased to 31.2 years of age (INE, 2017). In this period, women who become mothers mentioned family members, as the most important in family support, providing material or financial and emotional support and taking care of children (Rodrigues, 2008). Our qualitative research will enable pregnant women to describe the experience and main difficulties in this transition, allowing us to know their needs as Midwifes, developing appropriate interventions facilitating the transition to parenthood.